Ammonoid paleobiology: from anatomy to ecology - Klug, Christian; Korn, Dieter; De Baets, Kenneth; Kruta, Isabelle; Mapes, Royal H. (Topics in geobiology, 2015)
Part I. Conch -- Part II. Ontogeny -- Part III. Anatomy -- Part IV. Habit and habitats.
Description based upon print version of record
Keywords: Morphologie; Ontogenie; Palökologie; Ammoniten; Systematik; Paläontologie; Fossil; Paläobiogeografie